the one-to-one functions g and h are defined as follows. g={(-4, -5), (1, 2), (7,1), (8, 5)} find the following: g^-1(1)= ----- h^-1(x)= (h * h^-1) (5)=
Images:
This image has been Flagged as inappropriate
Click to unflag
- print Print
- list Cite
Expert Answers
Inna Shpiro
| Certified Educator
calendarEducator since 2013
write600 answers
starTop subjects are Math, Science, and Literature
In this question we need to find `g^(-1)` and `h^(-1)` , which are the inverse functions of the functions g and h, respectively.
The function g is given as a set of ordered pairs. To create inverse function `g^(-1)` , simply exchange x and y, or first and second coordinate, for each pair:
`g^(-1) = {(-5, -4), (2, 1), (1, 7), (5, 8)}`
Now we see that the value of `g^(-1)` of 1 is the second...
(The entire section contains 219 words.)
Unlock This Answer Now
Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.
Related Questions
- If f(x)=x+4 and h(x)=4x-1, find a function g such that g(f(x)) = h(x).
- 2 Educator Answers
- Use the functions f(x)=(1/8)x-3 and g(x)=x^3 to find the indicated value or function...
- 1 Educator Answer
- given h(x)= 4+1/ √ x-5 find the functions f and g that h(x)= (f o g)(x)
- 2 Educator Answers
- If f(x):=x+4 and g(x):= 4x-1, find a function g such that g x f=h
- 1 Educator Answer
- Given that f(5)=4, f'(5)=5, g(5)=9, g'(5)=8 Calculate (fg)'(5), (f/g)'(5), (g/f)'(5)
- 1 Educator Answer